Perbandingan Bentuk Antara Negara Federal, Negara Konfederasi, dan Negara Kesatuan dalam Prespektif Ilmu Negara - Dedi Mulyadi; Ira Putri Rahmasari; Zahra Mauliyah; Yudha Adhipratama; Asnita Anuar (Journal of Law Perspectives Review, 2025)
This article discusses a comparison between the forms of federal states, confederations, and unitary states from the perspective of the science of the state. The background of the study highlights the importance of understanding the differences in these governmental structures, as each form has a distinct system of power distribution. The research questions raised include the characteristics of each state form, differences in power distribution, and their impacts on governance and regional autonomy. The research method used is a literature study by analyzing theories in the science of the state and examining examples of countries that apply each form of government. The conclusion shows that federal states divide power between the central and regional governments, confederations emphasize the sovereignty of member states, while unitary states centralize power in the central government. Each system has its own advantages and disadvantages depending on the social, political, and cultural context of the respective country. This study also found that the choice of state form can influence political stability, resource management, and the relationship between the central and regional governments. Therefore, a comprehensive understanding of these governmental systems is essential in designing effective policies in a country.